Pengaruh Aspek Manajemen Keuangan Daerah Terhadap Transparansi Pengelolaan Keuangan Daerah di Lumajang - Ari Rachmad (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2021)
This study aims to verify the impact of aspects of regional financial management on the transparency of regional financial management in Lumajang. Primary data assortment was administered by distributing questionnaires. The collected data were then analyzed using linear regression. The study results explain that partially the aspects of regional financial planning, regional financial administration, reporting aspects, and regional financial supervision affect the transparency of regional financial management in Lumajang. Simultaneously the aspects of regional financial planning, aspects of regional financial administration, reporting aspects and aspects of regional financial supervision of the regions affect the transparency of regional financial management in Lumajang.